2019
DOI: 10.1371/journal.pone.0224993
|View full text |Cite
|
Sign up to set email alerts
|

Moving into an urban drug scene among people who use drugs in Vancouver, Canada: Latent class growth analysis

Abstract: BackgroundUrban drug scenes are characterized by high prevalence of illicit drug dealing and use, violence and poverty, much of which is driven by the criminalization of people who use illicit drugs (PWUD) and the associated stigma. Despite significant public health needs, little is understood about patterns of moving into urban drug scenes among PWUD. Therefore, we sought to identify trajectories of residential mobility (hereafter ‘mobility’) among PWUD into the Downtown Eastside (DTES), an urban neighbourhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Until recently, all the evidence on the effectiveness of supervised consumption sites in Canada was based on Vancouver’s Insite. First implemented in September 2003, Insite is in the Downtown Eastside – a unique neighborhood with one of the highest concentrations of people who use illicit drugs globally (Hayashi et al, 2019). Numerous studies have explored Insite’s effectiveness on drug related harms and acceptability in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, all the evidence on the effectiveness of supervised consumption sites in Canada was based on Vancouver’s Insite. First implemented in September 2003, Insite is in the Downtown Eastside – a unique neighborhood with one of the highest concentrations of people who use illicit drugs globally (Hayashi et al, 2019). Numerous studies have explored Insite’s effectiveness on drug related harms and acceptability in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Some identified indicators in the current study partly overlapped with indicators that have been previously reported by the EMCDDA and Pompidou group. Some DRCI indicators are not presented in the current study including poverty, street homelessness, the emergence of crack houses, attraction of new people to drug scene, and mental illness [2,4,47]. However, some indicators including street dealing, crime, discarded injecting equipment, and intimidation of citizens were common in previous reports and current studies [2,4,47].…”
Section: Direct and Indirect Indicatorsmentioning
confidence: 88%
“…Some DRCI indicators are not presented in the current study including poverty, street homelessness, the emergence of crack houses, attraction of new people to drug scene, and mental illness [2,4,47]. However, some indicators including street dealing, crime, discarded injecting equipment, and intimidation of citizens were common in previous reports and current studies [2,4,47]. Therefore, for arranging the indicators, they can potentially be categorized into direct and indirect indicators of DRCIs.…”
Section: Direct and Indirect Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is worth noting that >20% of the study population identified as Indigenous. In British Columbia and all of Canada, men and women of Indigenous descent are overrepresented in our inner cities and more likely to be disengaged from care [ 25 , 26 ]. It is a strength of our overall approach that we were able to identify, treat, and cure these patients.…”
Section: Discussionmentioning
confidence: 99%